Diamond/copper composite material and preparation method thereof - WANG ZHIQIANG; ZHANG RUI; ZHANG KAI; WANG HAILONG; SHAO GANG; LI MINGLIANG; SHAO JUNYONG (2022)
The invention discloses a preparation method of a diamond/copper composite material, and compared with a pressureless infiltration method and a spark plasma sintering method, the adopted oscillation hot pressing sintering method has the advantage that the diamond/copper composite material with higher interface bonding strength, higher heat conductivity and higher density can be prepared. Compared with the static pressure, the oscillating pressure can promote the particle rearrangement phenomenon of the diamond particles in the sintering process, and distribution of the diamond particles in the prepared diamond/copper composite material is more uniform. 本发明公开了一种金刚石/铜复合材料的制备方法，采用的振荡热压烧结方法，与无压熔渗法、放电等离子烧结法相比，具有能够制备出界面结合强度更高，热导率更高同时致密度更高的金刚石/铜复合材料。振荡压力相比于静态压力能够促进金刚石颗粒在烧结过程中发生颗粒重排现象，制备出的金刚石/铜复合材料中金刚石颗粒的分布更加均匀。